Statistics and data visualization in climate science with R and python - Shen, Samuel S. P.; North, gerald R. (New York Cambridge University press, 2023)
A comprehensive overview of essential statistical concepts, useful statistical methods, data visualization, and computing tools for the climate and related sciences. This book is an invaluable reference for students and researchers in climatology and its connected fields who wish to learn data science, statistics, R and Python programming. The examples and exercises in the book empower readers to work on real climate data from station observations, remote sensing and simulated results.